A review of existing codes and standards on design factors for UHPC placement and fiber orientation. (22nd August 2022) - Islam, Md. Mashfiqul; Zhang, Qian; Jin, Qingxu
Highlights: Review different construction procedure and their effects on fiber orientation. Review existing UHPC design codes and their consideration of fiber orientation. Recommendation on following UHPC design codes regarding fiber orientation. Identify future research on construction procedure to ensure fiber orientation. Abstract: Ultra-high-performance concrete (UHPC) has been extensively researched and implemented in various infrastructure applications for its superior structural and durability performance. Despite their successful structural level demonstrations, fiber dispersion and orientation remain a concern in the UHPC structure design. The casting flow direction, formwork geometry, rebar arrangement, use of casting device, and rheology of the mixtures are all reported to affect the fiber orientation and ultimately the structural performance of the UHPC members. A number of UHPC design codes and guidelines have been published by professional organizations across different countries, and the effect of fiber orientation were considered in several distinct ways in these specifications. In this article, a comprehensive review was conducted on the influence of various factors on the fiber orientation in structural elements. Existing structural design guidelines on UHPC, and steel fiber reinforced concrete materials from France, Germany, Japan, South Korea, Canada, Switzerland, Australia, and the U.S. were reviewed with a focus on their respective methods to account for the effect of fiber dispersion and orientation. Several design codes introduced separate design reduction factors to compensate the effect of undesirable fiber orientation. The background work and underlying rationale of these design factors were also included in this paper. Recommendations to the design professionals and for future research directions were provided at the end of the paper.